Case Report: Locally advanced lung adenocarcinoma with a novel MIR217HG-ALK rearrangement responding to neoadjuvant alectinib - Yinyin Xue; Yinyin Xue; Wen Li; Wen Li; Kaili Huang; Kaili Huang; Qinghua Zhou; Qinghua Zhou; Qiang Wu; Qiang Wu (Frontiers in Pharmacology)
BackgroundAnaplastic lymphoma kinase (ALK) rearrangement is a crucial oncogenic driver in non-small cell lung cancer (NSCLC). ALK tyrosine kinase inhibitors (ALK-TKIs) represent the primary therapeutic option for advanced NSCLC patients with ALK rearrangements. However, the definitive determination of ALK-TKIs sensitivity towards newly identified rare ALK rearrangements remains elusive. Herein, we present a patient with lung adenocarcinoma harboring a novel ALK rearrangement who exhibited major pathological response (MPR) following neoadjuvant treatment with alectinib.Materials and methodsWe conduct immunohistochemistry (IHC) staining with Ventana with D5F3 clone, fluorescence in situ hybridization (FISH, The Vysis ALK Break Apart FISH Probe Kit), and next-generation sequencing (NGS) analyses (Burning Rock, Guangzhou, China) on biopsy sample obtained from the patient.ResultsThe patient, a 66-year-old female, was diagnosed with stage IIIB-N3 adenocarcinoma in the right upper lobe of the lung. NGS testing revealed a previously unreported MIR217HG-ALK rearrangement, which was subsequently confirmed by IHC and FISH. Following 5 months of neoadjuvant treatment with alectinib, the patient underwent the right upper lobectomy and achieved MPR, resulting in disease-free survival (DFS) exceeding 19 months.ConclusionIn this study, we present the first documented case of a patient with lung adenocarcinoma harboring a novel MIR217HG-ALK rearrangement who exhibited favorable response to neoadjuvant alectinib. Our findings suggest that alectinib holds promise as an efficacious therapeutic option for individuals with MIR217HG-ALK rearranged lung adenocarcinoma, thereby offering valuable insights for the clinical management of these patients.